TRANSLATION ANALYSIS OF BALINESE TERMS EXPRESSING SOCIAL CULTURAL ASPECTS - Purnama, Ida Ayu Eka (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 20 (2013): September 2013, 2013)
There are several factors that make a translation is not easy to do especially in translating the terms that contain aspects of culture as it is known that there are cultural differences between the source language and the target language culture.This study aims to describe the translation procedure and the factors that affect the translation of Balinese cultural terms expressing social organization aspects including the religion, organization, art, and addressing terms which are translated into English. The result is there are some procedures applied by the translator to translate the Balinese cultural terms contain cultural organization aspects; borrowing, literal translation, modulation, equivalence and adaptation.Then, the factors that determine the translator applied those procedures in translating Balinese cultural terms expressing social organization aspects are the linguistic, culture, and translator’s preferences factors.
Keywords: translation procedures, social organization aspect, translation factors